Effect of Magnetic Field Inhomogeneity on Ion Cyclotron Motion Coherence at High Magnetic Field. Issue 3 (June 2015) - Vladimirov, Gleb; Kostyukevich, Yury; Hendrickson, Christopher L.; Blakney, Greg T.; Nikolaev, Eugene
A three-dimensional code based on the particle-in-cell algorithm modified to account for the inhomogeneity of the magnetic field was applied to determine the effect of Z 1, Z 2, Z 3, Z 4, X, Y, ZX, ZY, XZ 2 YZ 2, XY and X 2 –Y 2 components of an orthogonal magnetic field expansion on ion motion during detection in an FT-ICR cell. Simulations were performed for magnetic field strengths of 4.7, 7, 14.5 and 21 Tesla, including experimentally determined magnetic field spatial distributions for existing 4.7 T and 14.5 T magnets. The effect of magnetic field inhomogeneity on ion cloud stabilization ("ion condensation") at high numbers of ions was investigated by direct simulations of individual ion trajectories. Z 1, Z 2, Z 3 and Z 4 components have the largest effect (especially Z 1 ) on ion cloud stability. Higher magnetic field strength and lower m/z demand higher relative magnetic field homogeneity to maintain cloud coherence for a fixed time period. The dependence of mass resolving power upper limit on Z 1 inhomogeneity is evaluated for different magnetic fields and m/z. The results serve to set the homogeneity requirements for various orthogonal magnetic field components (shims) for future FT-ICR magnet design.